Using Website as a Source of Information on the Management of Health and Emergency Situations in Early Childhood - Sinaredi, Betadion Rizki; Pradhitta, Rezka Ajeng; Septianingtyas, Virna (Indonesian Journal of Dental Medicine, 2020)
Background: Currently online health promotion can be found on various sites and social media. Health promotion in the form of health education using the internet is considered easier, faster, and cheaper. However, not many websites provide information about health and emergency management in children. Purpose: The implementation of community empowerment aims to increase the knowledge of parents and teachers in managing the health and emergencies of children aged 2-6 years online using the media website. Methods: Online health education is provided to participants as a form of community empowerment. Participants receive a website address that contains material on child health and emergency management. Furthermore, participants received an explanation of the material using the zoom application. The level of participant knowledge was evaluated by pre-test and post-test using Google form. The evaluation results were analyzed descriptively. Results: Online health education activities with website media showed an increase in teachers' knowledge about health and emergency management in children (87.5%). This program also shows a decrease in the number of parents and teachers with low level knowledge (12.5%). Conclusion: The website can be used as an effective medium to provide health education for parents and teachers.